Mechanisms of junctional tachycardia showing ventricular pre-excitation. Issue 4 (October 1984) - Ward, D E; Bennett, D H; Camm, J
Abstract : Over a period of five years 12 patients underwent electrophysiological studies for the investigation of recurrent tachycardias which showed ventricular pre-excitation. Nine patients had a type B pattern and two a type A. One patient had episodes of both types. Dual atrioventricular nodal pathways were found in six of seven patients with atrioventricular nodal re-entrant tachycardia mechanisms. Single direct atrioventricular accessory pathways were present in four patients, single nodoventricular pathways in five, and multiple pathways in three. Twenty one tachycardias were induced, of which 13 showed ventricular pre-excitation. Five patients had nodoventricular pathway conduction during atrioventricular nodal tachycardia and one during atrioventricular re-entrant tachycardia. Only three patients had simple antidromic tachycardia and one additional atrioventricular nodal tachycardia with bystander atrioventricular accessory conduction. Three patients had three different tachycardias, three had two types, and six had one type. Thus junctional tachycardias showing ventricular pre-excitation are often associated with multiple mechanisms and complex anatomical and functional substrates. An accessory pathway was an essential component in only six of 13 tachycardias showing ventricular pre-excitation. Determination of the tachycardia mechanism requires detailed study and analysis.